2010
DOI: 10.3855/jidc.1217
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of enterotoxigenic and Shiga toxin-producing Escherichia coli in pigs slaughtered in Mato Grosso, Brazil

Abstract: Introduction: This study aimed to estimate the prevalence of enterotoxigenic Escherichia coli (ETEC) and Shiga toxin-producing Escherichia coli (STEC) strains in pigs slaughtered in abattoirs located in the state of Mato Grosso, Brazil. Methodology: Intestinal samples from 74 animals were aseptically dissected and lumen content was plated on MacConkey agar. Confluent colonies from each plate were screened for the presence of ETEC and STEC strains by PCR assays. Results: It was verified that the prevalence of S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
1
3

Year Published

2013
2013
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 21 publications
1
7
1
3
Order By: Relevance
“…In the present study most of the isolates possessed stx2 which is in accordance with the results reported in Argentina (Blanco et al, 2004), China (Zheng et al, 2005;Koitabashi et al, 2008), Japan (Kawano et al, 2012) and Denmark (Nielsen et al, 2002). Lower prevalence rates were reported in Brazil (1.35%; Martins et al, 2011) and India (11%; Khan et al, 2002). Furthermore, the results of this study showed that in addition to stx2 as the predominant gene, eaeA gene was the second most detected gene from STEC isolates.…”
Section: Discussionsupporting
confidence: 81%
“…In the present study most of the isolates possessed stx2 which is in accordance with the results reported in Argentina (Blanco et al, 2004), China (Zheng et al, 2005;Koitabashi et al, 2008), Japan (Kawano et al, 2012) and Denmark (Nielsen et al, 2002). Lower prevalence rates were reported in Brazil (1.35%; Martins et al, 2011) and India (11%; Khan et al, 2002). Furthermore, the results of this study showed that in addition to stx2 as the predominant gene, eaeA gene was the second most detected gene from STEC isolates.…”
Section: Discussionsupporting
confidence: 81%
“…Os suínos não são considerados a principal fonte de E. coli produtoras de toxinas de Shiga (STEC) pelo fato de terem uma prevalência normalmente muito baixa, enquanto as E. coli produtoras de LT e ST normalmente são isoladas de suínos com diarreia pós-desmame (Martins et al, 2010). Genes codificadores de toxinas são comumente isolados em casos de suínos com diarreia (Menin et al, 2008), mas a identificação de genes de toxinas em suínos hígidos não é tão frequente (Kaper et al, 2004).…”
Section: 2 3 4 5 6 7 8 N 480bp 244bpunclassified
“…Schierack et al (2006), em trabalho com suínos hígidos, encontraram 8,5% de cepas contendo apenas gene para STa e 3,9% somente para LT-I, valores próximos aos encontrados neste estudo. Valores semelhantes também foram encontrados por Martins et al (2010), que estudaram a prevalência de E. coli com genes para enterotoxinas em suínos de abatedouros no Mato Grosso e isolaram 1,35% de cepas positivas para Stx 2 ; 6,76% de cepas positivas para STa apenas; e 2,70% com genes de STa e LT-I associadas. Estes números demonstram uma baixa -porém existente -presença de genes de enterotoxinas de cepas isoladas em animais hígidos.…”
Section: 2 3 4 5 6 7 8 N 480bp 244bpunclassified
See 1 more Smart Citation
“…A minimum sample size of 14 animals was obtained per abattoir. Collection and processing of gut samples were previously described (Martins, Silva, Dutra, Nakazato, & Leite, 2011). Briefly, an ileum fragment of approximately 5 cm was sampled from each animal immediately after evisceration.…”
Section: Sampling Procedures and E Coli Isolationmentioning
confidence: 99%